2023
DOI: 10.1002/jez.2681
|View full text |Cite
|
Sign up to set email alerts
|

mRNA m6A methylation in wood frog brain is maintained during freezing and anoxia

Abstract: Freeze tolerance is an adaptive strategy that wood frogs (Rana sylvatica) use to survive the subzero temperatures of winter. It is characterized by a variety of metabolic and physiological changes that facilitate successful freezing and anoxia. As both mRNA regulation and posttranslation protein modification have been implicated in freeze tolerance, we hypothesized that posttranslational RNA regulation is also involved in coordinating freeze‐thaw cycles and metabolic rate depression. As such, we investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…For example, the study by Mareen Engel et al group reported that METTL3 was upregulated in the amygdala (AMY) after acute stress [ 21 ], which rescued the synaptic plasticity impairment as time goes on via upregulating the m6A methylation of its target gene Ntrk1, Creb1, and Nr3c1 in the hippocampus, suggesting that METTL3 upregulation in AMY is closely related to maintaining synaptic plasticity [ 21 ]. In addition, a study on the freezing and anoxia of the wood frog brain indicated that METTL3 was significantly upregulated, coupled with a significant increase in stress granule (SG) markers TIAR and TIA-1, indicating the beneficial role of METTL3 in balancing synaptic plasticity to confront the low-oxygen stress [ 22 ]. Moreover, loss of Mettl3 decreased the levels of nuclear Ythdc1, which in turn leads to stress resilience.…”
Section: Mettl3 In Neurophysiological Eventsmentioning
confidence: 99%
“…For example, the study by Mareen Engel et al group reported that METTL3 was upregulated in the amygdala (AMY) after acute stress [ 21 ], which rescued the synaptic plasticity impairment as time goes on via upregulating the m6A methylation of its target gene Ntrk1, Creb1, and Nr3c1 in the hippocampus, suggesting that METTL3 upregulation in AMY is closely related to maintaining synaptic plasticity [ 21 ]. In addition, a study on the freezing and anoxia of the wood frog brain indicated that METTL3 was significantly upregulated, coupled with a significant increase in stress granule (SG) markers TIAR and TIA-1, indicating the beneficial role of METTL3 in balancing synaptic plasticity to confront the low-oxygen stress [ 22 ]. Moreover, loss of Mettl3 decreased the levels of nuclear Ythdc1, which in turn leads to stress resilience.…”
Section: Mettl3 In Neurophysiological Eventsmentioning
confidence: 99%